Analysis of Internal Quality and Cognitive Distribution in Grade VII MTs Arabic Textbook: English - Misbahul Umam umam; Muhammad Alfan; Ibnu Samsul Huda; Laily Maziyah (Universitas Djuanda, 2026)
لم تعد المواد التعليمية تُعتبر مجرد أدوات أدبية سلبية في البيئة المدرسية، بل تحولت بالتزامن مع الانتشار الواسع لـ